TYPES OF MEDICINAL PLANTS IN THE GUNUNG LEUSER NATIONAL PARK AREA, KETAMBE VILLAGE, KETAMBE DISTRICT, SOUTHEAST ACEH - Kurniawati Kurniawati; Nursafiah Nursafiah; Mairi Sukma (Jurnal Biologi Sains dan Kependidikan, 2024)
The village of Ketambe is one of the villages that bordered directly the national park of mount leuser (TNGL). This allows for an intrusion of  Ketambe village people with forest in the vicinity of TNGL. Such an intraction form is about using plants as a tradisonal remedy. The purpose of this study is to identify the use, and the efficacy of drug abuse. The method used in this research is an overwhelming-sampling method. Studies that communities have benefited from the medicinal use of plants as many as 46 plants, from the 33 families believed to cure 28 diseases and additities found by 39 species from 29 familias. The most dominant part of the plant is leaves as many as 14 species (30.4 %), and the processing often done by milling (23.9 %). There are more than 85 different plants found from 46 tribes, euphorbiaceae has a high number of 9 (10.4 %).